Coincidence time resolution of radiation detector based on 6×6 mm2 ToF SiPM detectors with different readout schemes - Li, Changyu; Li, Yuying; Xi, Jianbo; Xiang, Shitao; Hu, Kun (Frontiers in Physics, 2023)
Nowadays, attention is growing on the Silicon Photomultipliers (SiPMs) detector for many applications, especially in nuclear medicine research. Currently, timing performance in Positron Emission Tomography (PET) detector plays a significant role in image reconstruction. This work mainly aims at the processing of timing signal for a better timing performance. We applied a timing detector with a 3×3×10 mm3 LYSO crystal directly coupled with a large-size SensL SiPM with a sensitive area of 6×6 mm2. The standard output of the SiPM was used for energy calculations while the fast output was for timing pickoff. Three different readout configurations for fast timing signals were used for timing performance evaluation: 1) the recommended RF transformer-based readout, 2) the cascaded Common Emitter Amplifier (CEA), 3) the commercial RF amplifier. The best FWHM CTR values for the three were 228.3 ± 1.4 ps, 235.4 ± 1.1 ps and 231.1 ± 1.5 ps for the RF transformer-based, the CEA-based and the RF amplifier-based readout configurations respectively. Experiment results show that schemes based on the CEA-based and the RF amplifier-based configuration have a better uniformity with different trigger thresholds, which is better for practical multi-channel readout electronics system.